Determinants of the spread between POLONIA rate and the reference rate – dynamic model averaging approach - Kliber, Paweł (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
In the paper, we consider the factors that determine the overnight interest rates in the Polish interbank market. Since 2008 the Polish central bank has been trying to place the POLONIA rate around the NBP reference rate, mainly by influencing the liquidity conditions through open market operations. We identify a set of factors that determine the overnight rates, namely: liquidity, expectations, confidence in the banking sector and central bank operations. To this end we have used dynamic model averaging method, which allows to identify the set of variables that provide the best description of the explanatory variable. The results reveal that before the outbreak of financial crisis in 2008 the spread between POLONIA rate and reference rate could be explained mainly by liquidity conditions. After the crisis had begun, the importance of liquidity factor decreased and the expectations played a more important role in determining the spread
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2017, Nr 482, s. 107-120
Keywords: monetary policy; POLONIA rate; interbank rates; dynamic model averaging; liquidityin the interbank market; polityka monetarna; stawka POLONIA; stopy międzybankowe; dynamiczne uśrednianie modeli; płynność na rynku międzybankowym